Agricultural Innovation Systems: An Investment Sourcebook - M'Randa R. Sandlin; J Thomas Wynn (Journal of International Agricultural and Extension Education, 2014)
The World Bank assembled this reference guide to explain the contributing aspects and limitations of the Agricultural Innovation System (AIS). The guide is divided into seven modules to better address topics through detailed overviews, recommended approaches and programs, and successful activities for each. The first module stresses the importance of a collaborative effort in a successful AIS structure, specifically, national coordination and governance, building innovation networks, increasing access to marketing chains, and building innovation capabilities in farmer organizations. Module 2 delves into the role of agricultural education and training as “a creator of capacity and supplier of the human resources that populate key segments of the AIS and enable that system to function more effectively” (Maguire, 2012, p. 107).
Keywords: Agricultural Innovation System; AIS; Case Study Research; Public Private Partnerships